(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Thrombotic phenomena are multifactorial phenomena with both acquired and inherited factors. Factor V Leiden (FVL) and G20210A mutation of prothrombin (FIIG20210A) are the most studied inherited factors, with a prevalence that varies by population and race, high in Europe and almost nil in Asian countries. Information concerning the prevalence of these mutations in Chile is scarce. The aim of this study was to determine the prevalence of FVL and FII G20210A mutation in patients with a history of thrombotic events in the city of Temuco, Araucanía region. Genetic analysis for FVL Thrombophilia and FIIG20210A mutation was performed from January 2012 to December 2013.Three hundred thirty-three screenings by PCR in real time and the genotype of each mutation were determined and analyzed by Melting curve. We found an average prevalence of 2.28% for the FVL, whereas FIIG20210A mutation was 6.49%. No mutations were found in homozygous state. Both mutations are present in our population, it is therefore important to evaluate the risk associated with their presence in patients with a history of thrombotic events. In our specific population FII G20210A mutation is highly prevalent, thus genetic studies should be realized or requested.